Pharmacokinetic profile of amodiaquine and its active metabolite desethylamodiaquine in Ghanaian patients with uncomplicated Falciparum malaria - Anyorigiya, Thomas Atingane (Division of Clinical Pharmacology, 2018)
RATIONALE: The accurate measurement of antimalarial drug concentrations in key target patient groups is essential to ensure optimal dosing for malaria treatment and to distinguish between inadequate drug exposure and antimalarial resistance. METHODS: A sensitive and selective liquid chromatography-tandem mass spectrophotometric method was developed and validated for the simultaneous determination of amodiaquine and its active metabolite, desethylamodiaquine in 20μl heparinised human capillary whole blood and capillary plasma. During validation no significant matrix effects were observed for the analytes or internal standards. This assay method was successfully used to describe the pharmacokinetics of amodiaquine and desethylamodiaquine in Ghanaian patients with uncomplicated falciparum malaria, who were followed up for 28 days in a therapeutic efficacy study of the fixed-dose combination therapy, artesunate-amodiaquine. RESULTS: The day 28 genotype-adjusted adequate clinical and parasitological response rate of artesunate-amodiaquine combination in 321 patients studied was above 97% in both the intention-to-treat and per protocol analyses in the two study sites. Amodiaquine and desethylamodiaquine pharmacokinetic parameters were defined for 225 patients (7 infants, 127 aged 1-4 years, 91 aged ≥5 years). Multivariate analysis of the effects of pre-defined covariates found that mg/kg dose, female gender, hyperparasitaemia and site of sample collection were independently associated with desethylamodiaquine pharmacokinetic parameters. Although the association between treatment outcome and desethylamodiaquine day 7 concentrations or area under the concentration-time curve could not be established due to high artesunate-amodiquine efficacy, median day 3 amodiaquine concentrations were associated with 13% reduction in the rate of parasite recurrence, p=0.021. Despite the significantly higher amodiaquine exposure (4988ng.h/ml, p<0.001) in infants compared to the older age groups, no significant safety concerns were identified. The ratio of the geometric mean of matched concentrations in capillary whole blood to capillary plasma in a subset of 163 field samples was approximately 2.04 [95% CI 1.90-2.19] for amodiaquine and 2.4 [95%CI 2.14-2.63] for desethylamodiaquine. CONCLUSION: Pharmacokinetic parameters of amodiaquine and desethylamodiaquine were determined in the largest single uncomplicated malaria pharmacokinetic study to date. Although efficacy was high across all age groups with currently recommended dosage regimens, factors were identified as potentially significant covariates that may require further investigation in pooled analyses.